The influence of urban poverty on students’ academic optimism: does government assistance play a role? - Othman, Azam; Mohd Ali, Hairuddin; Hussien, Suhailah; Abdullah, Moha Asri; Ruslan, Norbaiduri; Souad, Merah (IIUM Press, 2021)
The present study investigated the relationship between urbanpoor students’ perceptions of government assistance and poverty and their level of academic optimism. A survey was administered to 500 urban poor students in two major Malaysian cities, Kuala Lumpur and Johor Bahru. The students were identified and randomly selected for the study with the help of their respective schools.AMOS version 24 was used to test the hypothesised model using Structural Equation Modelling (SEM). The findings revealed a significant direct association between students’ perceptions of poverty and academic optimism. However, no significant indirect influence was found between students’ perceptions of poverty and their academic optimism through government assistance. These findings suggest that government assistance programmes are not necessarily a contributor to students’ academic optimism. The lack of any significant influence between students’ perceptions of poverty and academic optimism, through government assistance, may indicate a need to re-evaluate the existing assistance programmes rendered by the government to students in the urban poor category